Genome-Wide Analysis of Wound-Induced Polypeptide Genes in Glycine max and Their Expression Dynamics During Cyst Nematode Infection - Wenshu Kang; Zicheng Sun; Jiayao Xu; Nawei Qi; Piao Lei (Agronomy)
Plant small peptides are critical regulators of various biological processes, including development and stress responses. Polypeptides within the DUF3774 family, known as wound-induced polypeptides (WIPs), have been identified as key players in pattern-triggered immunity (PTI) and defense mechanisms in Arabidopsis. In this study, the genome-wide identification of WIP genes in Glycine max was performed, followed by gene structure correction and validation using second-generation and full-length RNA sequencing data. A total of 31 GmWIP genes were identified and validated, mapped to chromosomes Gm06, Gm12, Gm13, and Gm06_scaffold_301. Phylogenetic analysis grouped these genes into five distinct clusters, with tandem duplication emerging as the primary mechanism for their expansion in the soybean genome. qRT-PCR analysis revealed dynamic and significant changes in GmWIP expression during soybean cyst nematode (SCN) infection in a susceptible soybean cultivar. Remarkably, 90% of the GmWIP genes were downregulated at the early stage of SCN infection (1 dpi), and further corroborated by the pGmWIPs::GUS reporter system. These findings suggest that GmWIP genes may act as regulators in the defense responses of susceptible soybean cultivars, providing a foundation for future functional studies.